Treatment effectiveness and fidelity of manual therapy to the knee: A systematic review and meta‐analysis. (18th November 2016) - Salamh, Paul; Cook, Chad; Reiman, Michael P.; Sheets, Charles
Abstract: Manual therapy (MT) is a commonly used treatment for knee osteoarthritis (OA) but to date only one systematic review has explored its effectiveness. The purpos e of the present study was to perform a systematic review and meta‐analysis of the literature, to determine the effectiveness and fidelity of studies using MT techniques in individuals with knee OA. Relevant studies were assessed for inclusion. Effectiveness was measured using effect sizes, and methodological bias and treatment fidelity were both explored. Effect sizes were calculated using standardized mean differences (SMD) based on pooled data depending on statistical and clinical heterogeneity, as well as risk of bias. The search captured 2, 969 studies; after screening, 12 were included. Four had a low risk of bias and high treatment fidelity. For self‐reported function, comparing MT with no treatment resulted in a large effect size (standardized mean difference [SMD] 0.84), as did adding MT to a comparator treatment (SMD 0.78). A significant difference was found for pain when adding MT to a comparator treatment (SMD 0.73). The findings in the present meta‐analytical review support the use of MT versus a number of different comparators for improvement in self‐reported knee function. Lesser support is present for pain reduction, and no endorsement of functional performance can be made at this time.